Knowledge and Beliefs on Mental Illness among Church Leaders: Basis for Training and Development - Del Rosario, Ma. Camille P.; Lacerna, Clarita; Castaños, Kyle Irvine O.; Fabon, Joseph; Malang, Bernandino P. (Future Science / FSH-PH Publications, 2023)
Mental health awareness and support have become increasingly important worldwide, including in the Philippines. In this context, religious institutions play a crucial role in shaping societal beliefs, attitudes, and approaches to mental illness. This study investigates the knowledge and beliefs about mental illness among church leaders in the Philippines, with a focus on five religious’ denominations: Jehovah’s Witnesses, Baptist, Born Again, Iglesia Ni Cristo, and Roman Catholic. One of the primary objectives of this research was to assess the level of knowledge church leaders possess regarding mental health. The findings indicate that church leaders in the Philippines have a moderate level of knowledge about mental health issues. The mean knowledge score, computed from their responses to a set of Likert-scale questions, falls into the category of